META ANALISIS PENERAPAN MODEL PEMBELAJARAN TWO STAY TWO STRAY TERHADAP PENINGKATAN HASIL BELAJAR IPA SISWA SEKOLAH DASAR - Veronica Venny Kusumawati; Firosalia Kristin (STKIP Persada Khatulistiwa Sintang, 2021)
This study aims to re-analyze the application of the Two Stay Two Stray model in improving the learning outcomes of elementary school students. This study uses a meta-analysis method. The author begins the research by searching for relevant journals to facilitate the author in the data collection process. The data is obtained through searching online journals through google scholar or google academia by writing the keywords Two Stay Two Stray, science learning outcomes, and elementary school. From the search conducted, the researcher obtained 25 journals and then the researcher chose 16 journals that match the author's criteria. The data that has been obtained will be processed again using quantitative methods. Based on the results of the analysis by applying the Two Stay Two Stray learning model in learning, it shows that this model can improve students' science learning outcomes with the lowest average value of 0.080% and the highest average value of 51.24%. The implementation of Two Stay Two Stray greatly affects the learning outcomes of elementary school students. In addition, students also have different habits in the teaching and learning process because they are required to think more critically and be open to friends. It can also improve students' understanding of the subject matter easily during the learning process.